The Culturally Intelligent Leader - Sean F Daly (Academic Chairpersons Conference Proceedings, 2023)
Research has shown that a culturally intelligent (CQ) leader will have a positive impact on organizational culture, satisfaction, productivity, and retention. Moreover, data shows that CQ has a strong positive relationship with job satisfaction and perceived transformational leadership. This training program is designed to help leaders develop a greater awareness of their motivation and understanding of cultural intelligence while also helping them to develop strategies and an action plan around improving their level of CQ. The suggested audience for this are experienced managers who have had some interaction with a culturally diverse population and want to serve their population better.
Keywords: leadership; cultural & amp; emotional intelligence; employee motivation